2019
DOI: 10.3390/toxins11070421
|View full text |Cite
|
Sign up to set email alerts
|

Daphnia magna Exudates Impact Physiological and Metabolic Changes in Microcystis aeruginosa

Abstract: While the intracellular function of many toxic and bioactive cyanobacterial metabolites is not yet known, microcystins have been suggested to have a protective role in the cyanobacterial metabolism, giving advantage to toxic over nontoxic strains under stress conditions. The zooplankton grazer Daphnia reduce cyanobacterial dominance until a certain density, which may be supported by Daphnia exudates, affecting the cyanobacterial physiological state and metabolites’ production. Therefore, we hypothesized that D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 80 publications
0
17
1
Order By: Relevance
“…Considering that the cyanobacteria and their genes responsible for toxin production are much older than complex organisms, such as their grazers, it has been suggested that an antigrazing role could have been obtained and kept over time due to grazing pressure (Wilken et al, 2010;Chislock et al, 2013). Increase of microcystin concentration in the presence of Daphnia infochemicals has been recorded in several studies (Jang et al, 2003(Jang et al, , 2007Izydorczyk et al, 2008;Kaplan et al, 2012;Pérez-Morales et al, 2015), as well as the higher export of microcyclamide 7806A (Sadler and von Elert, 2014a), and cyanopeptolin A (Bojadzija Savic et al, 2019) supporting this hypothesis. Cyanobacterial response seems to be strain dependant, as 4 out of 8 strains increased the production of microcystin in the presence of Daphnia medium (van Gremberghe et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Considering that the cyanobacteria and their genes responsible for toxin production are much older than complex organisms, such as their grazers, it has been suggested that an antigrazing role could have been obtained and kept over time due to grazing pressure (Wilken et al, 2010;Chislock et al, 2013). Increase of microcystin concentration in the presence of Daphnia infochemicals has been recorded in several studies (Jang et al, 2003(Jang et al, , 2007Izydorczyk et al, 2008;Kaplan et al, 2012;Pérez-Morales et al, 2015), as well as the higher export of microcyclamide 7806A (Sadler and von Elert, 2014a), and cyanopeptolin A (Bojadzija Savic et al, 2019) supporting this hypothesis. Cyanobacterial response seems to be strain dependant, as 4 out of 8 strains increased the production of microcystin in the presence of Daphnia medium (van Gremberghe et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Nevertheless, zooplankton often coexists with toxic cyanobacterial blooms, through co-acclimation, in mutual two-way interactions that are yet to be disentangled. It remains unclear whether Daphnia infochemicals could have negative impact on cyanobacterial growth and photosynthetic activity, due to contradicting results in the literature (Jang et al, 2007;Yang and Li 2007;Bojadzija Savic et al, 2019). Furthermore, whether cyanobacteria suffer from oxidative stress when exposed to daphnids requires further clarification.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Importantly, the use of spent medium or daphnid extracts allows only to study the effect of grazers on cyanobacteria while in situ a mutual interaction can occur, and possibly the array of molecules released by daphnids may be altered by the cyanobacteria presence. One should also note that the anti-grazing defense in Microcystis, including its non-MC producing strains, may also be attributed to other metabolites such as cyanopeptolin A or microcyclamide 7806A whose roles are much less studied (Sadler and von Elert, 2014;Bojadzija Savic et al, 2019, 2020. The present study employed only one strain of M. aeruginosa which was capable of MC-production.…”
Section: Discussionmentioning
confidence: 98%